The Lyotard reader and guide - Lyotard, Jean-François, 1924-1998; Chrome, Keith, 1965-; Williams, James, 1965- (Edinburgh : Edinburgh University Press, 2006)
The first comprehensive anthology of Jean-François Lyotard's writings together with a critical guide.
1. Taking the side of the figural -- 2. The great ephemeral skin -- 3. Presentation -- 4. The Postmodern Condition, chapters 10-12 -- 5. The affect-phrase -- 6. Answering the question: what is postmodernism? -- 7. Return upon the return -- 8. Soundproof Room, chapters 4-6 -- 9. Sendings -- 10. The state and politics in the France of 1960 -- 11. A short libidinal economy of a narrative set-up: the Renault Corporation relates the death of Pierre Overney -- 12. A memorial of Marxism: for Pierre Souyri -- 13. The communication of sublime feeling -- 14. Time today -- 15. The connivances of desire with the figural -- 16. Painting as a libidinal set-up (genre: improvised speech) -- 17. Newman: the instant -- 18. On what is 'art'
Includes bibliographical references (pages 351-354) and index.
Online resource; title from PDF title page (viewed March 7, 2022).
JSTOR
Keywords: Lyotard, Jean-François, -- 1924-1998 -- Criticism and interpretation; Lyotard, Jean François -- Critique et interprétation.; Lyotard, Jean-François, -- 1924-1998; PHILOSOPHY -- General; Criticism, interpretation, etc